Diethoxyacetate Salts as Co‐initiators for Radical Photosensitive Resins: Towards Aromatic Amine‐Free Systems?. Issue 11 (26th June 2019) - Abdallah, Mira; Al Mousawi, Assi; Nechab, Malek; Hijazi, Akram; Fouassier, Jean‐Pierre; Dumur, Frédéric; Lalevée, Jacques
Abstract: Diethoxyacetate salts are investigated as new co‐initiators for the free radical polymerization (FRP) of (meth)acrylates upon visible light exposure, with light emitting diodes (LEDs; 405 nm, 477 nm) being employed for this purpose. Interestingly, the impact of the counter cation on their initiating ability is clearly highlighted. When these co‐initiators are combined with commercial photoinitiators such as 2‐isopropylthioxanthone (ITX) or camphorquinone (CQ), good to excellent free radical polymerization initiating performances are found and high final reactive function conversions are achieved. In the absence of these co‐initiators, no or poor polymerization occurs, clearly highlighting the importance of these co‐initiators for an efficient process. These systems can be interesting for the replacement of aromatic amines opening the way for amine‐free Type II photoinitiating systems. Abstract : Diethoxyacetate salts were studied and proposed as new co‐initiators in combination with well‐established Type II photoinitiators for the free radical polymerization of (meth)acrylates upon irradiation with LEDs of wavelengths λ =405 nm and 477 nm. Remarkably, a new reported co‐initiator (CoI‐1) can be used for aromatic amine‐free systems.